(untitled) (Revista de Ensino em Artes, Moda e Design, 2023)
This article intends to present the first analyzes and insights obtained through the mapping of main trends for the national fashion sector. The objective of this study is to present the main trends in the business environment that are already impacting the clothing sector, and promise to consolidate in the coming years, anticipating important issues for businesses and professionals who wish to remain relevant in the market. We identify and highlight examples of national and international companies that are leading this change by proposing innovative actions and strategies. Through the analysis of secondary data and information collected from interviews with specialists in the sector, it was possible to identify movements, technological innovations, new consumer demands, among other issues, fundamental for business and for the competitiveness of the fashion sector.